Prions and prion diseases: Insights from the eye. (October 2020) - Singh, Neena; Chaudhary, Suman; Ashok, Ajay; Lindner, Ewald
Abstract: Prion diseases are invariably fatal neurodegenerative disorders that have gained much publicity due to their transmissible nature. Sporadic Creutzfeldt-Jakob disease (sCJD) is the most common human prion disorder, with an incidence of 1 in a million. Inherited prion disorders are relatively rare, and associated with mutations in the prion protein gene. More than 50 different point mutations, deletions, and insertions have been identified so far. Most are autosomal dominant and fully penetrant. Prion disorders also occur in animals, and are of major concern because of the potential for spreading to humans. The principal pathogenic event underlying all prion disorders is a change in the conformation of prion protein (PrP C ) from a mainly α-helical to a β-sheet rich isoform, PrP-scrapie (PrP Sc ). Accumulation of PrP Sc in the brain parenchyma is the major cause of neuronal degeneration. The mechanism by which PrP Sc is transmitted, propagates, and causes neurodegenerative changes has been investigated over the years, and several clues have emerged. Efforts are also ongoing for identifying specific and sensitive diagnostic tests for sCJD and animal prion disorders, but success has been limited. The eye is suitable for these evaluations because it shares several anatomical and physiological features with the brain, and can be observed in vivo during disease progression. The retina, considered an extension of the central nervous system, is involved extensively in prion disorders. Accordingly, Optical Coherence Tomography and electroretinogram have shown some promise as pre-mortem diagnostic tests for human and animal prion disorders. However, a complete understanding of the physiology of PrP C and pathobiology of PrP Sc in the eye is essential for developing specific and sensitive tests. Below, we summarize recent progress in ocular physiology and pathology in prion disorders, and the eye as an anatomically accessible site to diagnose, monitor disease progression, and test therapeutic options. Highlights: Prion protein (PrP C ) is expressed in the anterior & posterior segment of the eye. Absence of PrP C promotes endothelial to mesenchymal transition in TM cells. PrP C helps to maintain iron homeostasis in the anterior segment. Anterior segment maintains iron homeostasis independent of the retina. TGFβ2 and hepcidin form a positive feed-forward loop fueled by iron-catalyzed ROS.